The C-type lectin SIGNR1 binds Schistosoma mansoni antigens in vitro, but SIGNR1-deficient mice have normal responses during schistosome infection - FALLON, PADRAIC (American Society for Microbiology, 2009)
The de novo immune response to infectious organisms arises from the innate recognition of pathogen-associated molecular patterns (PAMPs) by the host's pattern recognition receptors (PRRs). As the generation of type 2 cytokine responses by the human trematode parasite Schistosoma mansoni is glycan mediated, there is a particular potential role for a C-type lectin receptor (CLR) to mediate the innate recognition of schistosome PAMPs. One such CLR, dendritic cell-specific intracellular adhesion molecule-3-grabbing nonintegrin (DC-SIGN; CD209), has been shown to recognize glycans expressed by S. mansoni eggs. We show that SIGNR1 (SIGN-related 1; CD209b), a murine homologue of DC-SIGN that is expressed on macrophages, also binds both schistosome-soluble egg antigens and worm antigens in vitro. The generation of schistosome egg-induced pulmonary egg granulomas was not altered in SIGNR1-deficient mice. Following S. mansoni infection, the SIGNR1-deficient mice had an unaltered phenotype with an intact immunological response and no difference in pathology. In this study we demonstrate that although SIGNR1 recognizes S. mansoni antigens in vitro, this CLR is redundant during infection. This study highlights the finding that although there was binding of SIGNR1 to immunogenic factors produced in the S. mansoni life cycle, this recognition does not translate to a functional in vivo role for the PRR during infection.
PUBLISHED
Keywords: Clinical Medicine